Women's Empowerment in Jordan: Climate, and Development Policy Gap Analysis and Assessment - Albaddawi, Eman (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to systematically analyze main climate adaptation, economic, and developmental policies in Jordan to uncover how the concept of women's empowerment and see how it was incarnated in in these strategic policy documents. Specifically, the study examines 15 key national climate and developmental policies, with particular attention to women's engagement in entrepreneurial and income-generating activities Methods: The study used the gap analysis approach to analyze the policy documents, integrating a self-designed thematic gap analysis model to investigate contextual elements within the policies. This model seamlessly merged an initial keyword search phase with a subsequent detailed thematic coding process, offering a comprehensive understanding of how women's empowerment and entrepreneurship were incarnated and addressed within the policy documents. Results: The study results suggested that women are positioned well in climate policy; however, efforts to delineate women's empowerment on a regional basis through the implementation of green energy solutions appear to be missing. In addition, while women's economic empowerment through entrepreneurship in vulnerable communities was recognized, it lacks depth and adequate consideration, particularly in financing mechanisms. Conclusions: The study examined that pivotal policies in Jordan underscore the significance of women's participation in crafting enduring climate and developmental strategies. While the investigation underscored shortcomings in certain aspects (such as the integration of green growth and financial mechanisms), the study recommends that collaborative consultation with external experts is advised to bolster these policies. Additionally, capacity-building efforts targeting the most vulnerable communities, particularly in modern entrepreneurial tools and practices, are recommended to foster more efficient economic activities